Variation in available micronutrients in black soil after 30-year fertilization treatment - Y.G. Zhang; Y.Y. Zhang; J.P. Cai; P. Zhu; H.J. Gao; Y. Jiang (Plant, Soil and Environment, 2014)
To assess the effects of long-term fertilization on soil available micronutrients in farmland, this study examined diethylenetriaminepentaacetic acid (DTPA) extractable iron (Fe), manganese (Mn), copper (Cu), and zinc (Zn) in surface soil with monoculture of corn (Zea mays L.) with a 30-year filed fertilization experiment established in Northeast China. Treatments included no fertilization (CK); nitrogen only (N); nitrogen and phosphorus only (NP); NP and potassium (NPK); NPK plus cornstalk (SNPK), and NPK plus farmyard manure (MNPK). Results showed that DTPA-Fe and Mn were significantly increased with chemical N application, and DTPA-Cu and Zn were significantly increased with farmyard manure amendment, while micronutrients were not significantly different between treatment SNPK and CK. DTPA-Fe and Mn were about twice to threefold in treatments N, NP, and NPK as much as in treatments SNPK, MNPK and CK. DTPA-Cu and Zn in treatment MNPK were about 3.9 and 6.5 times as much as in CK. DTPA-Fe and Mn decreased with the increasing of soil pH and cation exchange capacity, while DTPA-Cu and Zn increased with the increase of soil organic carbon and electrical conductivity.